Prevalence and correlates of food insecurity in rural Nigeria: A panel analysis - Oluwakemi Adeola Obayelu; Emem Ime Akpan; Ayodeji O. Ojo (Economia Agro-Alimentare, 2021)
The study assessed dynamics of food insecurity among households in rural Nigeria using the Living Standard Measurement Survey-Integrated Survey on Agriculture (LSMSISA) collected in 2010/2011 and 2015/2016. Food insecurity status of the households was constructed using Household Food Insecurity Access Scale and analysed with descriptive statistics and random effect ordered probit model. Overall, 63.10%, 26.24%, 9.53% and 1.13% of households were food secure, mildly food insecure, moderately food insecure and severely food insecure, respectively in the first panel; while 46.53%, 31.63%, 19.39% and 2.45% were food secure, mildly food insecure, moderately food insecure and severely food insecure, respectively in the second panel. Food insecurity status increased with large household size, dependency ratio, being female-headed and aging household heads. Households in south-eastern Nigeria had a higher food insecurity incidence than elsewhere. Age, age squared, female to male adult ratio, primary and tertiary education, occupation, marital status, household size, access to credit and living in North East, North West, South West, South East and South zones were the correlates of food insecurity in rural Nigeria. Based on the findings, the study recommended an increased awareness on the use of family planning methods and improved access to family planning services. Also, severely food insecure households should be identified and specifically targeted by the government for appropriate safety net interventions.